Variability in Diagnosis and Management of Hypoglycemia in Neonatal Intensive Care Unit - Dinu, Daniela; Hagan, Joseph L.; Rozance, Paul J. (American Journal of Perinatology, 2024)
Objective Hypoglycemia, the most common metabolic derangement in the newborn period remains a contentious issue, not only due to various numerical definitions, but also due to limited therapeutical options which either lack evidence to support their efficacy or are increasingly recognized to lead to adverse reactions in this population. This study aimed to investigate neonatologists' current attitudes in diagnosing and managing transient and persistent hypoglycemia in newborns admitted to the Neonatal Intensive Care Unit (NICU).Methods A web-based electronic survey which included 34 questions and a clinical vignette was sent to U.S. neonatologists.Results There were 246 survey responses with most respondents using local protocols to manage this condition. The median glucose value used as the numerical definition of hypoglycemia in first 48 hours of life (HOL) for symptomatic and asymptomatic term infants and preterm infants was 45 mg/dL (2.5 mmol/L; 25–60 mg/dL; 1.4–3.3 mmol/L), while after 48 HOL the median value was 50 mg/dL (2.8 mmol/L; 30–70 mg/dL; 1.7–3.9 mmol/L). There were various approaches used to manage transient and persistent hypoglycemia that included dextrose gel, increasing caloric content of the feeds using milk fortifiers, using continuous feedings, formula or complex carbohydrates, and use of various medications such as diazoxide, glucocorticoids, and glucagon.Conclusion There is still large variability in current practices related to hypoglycemia. Further research is needed not only to provide evidence to support the values used as a numerical definition for hypoglycemia, but also on the efficacy of current strategies used to manage this condition.Key Points
Keywords: hypoglycemia; hyperinsulinism; NICU; dextrose gel; diazoxide; complex carbohydrates; glucocorticoids